Advances in Research in STEM Education - Kalogiannakis, Michail; Ampartzaki, Maria (IntechOpen, 2022)
Along with focusing on advances that bring forward STEM education, this book presents research on a variety of issues related to the STEM approach. Chapters discuss strategies in STEM teaching and learning as well as strategies that help students cope with the challenges of hard mathematical work. They also address problems of resource purchasing and factors that impact girls' decisions to pursue STEM careers. Through these and other topics, this book seeks to facilitate a deeper understanding of STEM education and its challenges in the contemporary world.